Biofilm-Forming Ability of Phytopathogenic Bacteria: A Review of its Involvement in Plant Stress - Carezzano, Maria Evangelina (2023)
Phytopathogenic bacteria not only affect crop yield and quality but also the environment. Understanding the mechanisms involved in their survival is essential to develop new strategies to control plant disease. One such mechanism is the formation of biofilms; i.e., microbial communities within a three-dimensional structure that offers adaptive advantages, such as protection against unfavorable environmental conditions. Biofilm-producing phytopathogenic bacteria are difficult to manage. They colonize the intercellular spaces and the vascular system of the host plants and cause a wide range of symptoms such as necrosis, wilting, leaf spots, blight, soft rot, and hyperplasia. This review summarizes up-to-date information about saline and drought stress in plants (abiotic stress) and then goes on to focus on the biotic stress produced by biofilm-forming phytopathogenic bacteria, which are responsible for serious disease in many crops. Their characteristics, pathogenesis, virulence factors, systems of cellular communication, and the molecules implicated in the regulation of these processes are all covered.